1991
DOI: 10.3382/ps.0701362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgical and Chemical In Ovo Bursectomy on Lymphocyte Density Scores and Histological Evaluations of Primary and Secondary Lymphoid Organs in Hypertensive and Hypotensive Turkeys

Abstract: The effects of surgical and chemical in ovo bursectomy on the histology of primary and secondary lymphoid organs were studied in hypertensive and hypotensive lines of turkeys. The effects of bursectomy were measured by determining the presence of lymphatic nodules and the presence of lymphocytes in secondary lymphoid organs: spleen, cecal tonsil, Meckel's diverticulum, and Peyer's patches; as well as in the thymus and bursa of Fabricius. No treatment effect on splenic nodule formation occurred, but a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The development, maturation, and differentiation of B-cells in birds depend on the normal structure of the BF [ 3 ]. In an earlier report, it was demonstrated that surgical bursectomy or chemical removal of the BF profoundly disrupts the normal process of B-cell development, thereby seriously inhibiting the immune function of the BF [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development, maturation, and differentiation of B-cells in birds depend on the normal structure of the BF [ 3 ]. In an earlier report, it was demonstrated that surgical bursectomy or chemical removal of the BF profoundly disrupts the normal process of B-cell development, thereby seriously inhibiting the immune function of the BF [ 4 ].…”
Section: Introductionmentioning
confidence: 99%